A117 CHARACTERIZATION OF A NOVEL GAIN OF FUNCTION MUTATION IN A NON-RECEPTOR TYROSINE KINASE IN THE DEVELOPMENT OF VERY EARLY ONSET INFLAMMATORY BOWEL DISEASE. (15th March 2019) - Mehta, M; Wang, L; Li, Q; Warner, N; Pan, J; Muise, A
Abstract: NOT PUBLISHED AT AUTHOR'S REQUEST Funding Agencies: CAG, CCC, CIHRHelmsley Charitable Trust, Chinese Government Scholarship